1997
DOI: 10.1042/cs0930355
|View full text |Cite
|
Sign up to set email alerts
|

Selective Migration of α-Smooth Muscle Actin-Positive Myofibroblasts toward Fibronectin in the Boyden's Blindwell Chamber

Abstract: 1. In order to address the hypothesis that migrating fibroblasts have a different phenotype, human fetal lung fibroblasts (HFL-1) cells were evaluated in the Boyden blindwell chamber migration assay followed by immunoelectron microscopy. 2. HFL-1 cells were placed on nucleopore filters and incubated for 2 h using purified human plasma fibronectin (pFn) as a chemoattractant. Filters were then processed for immunoelectron microscopy using antibodies for alpha-smooth muscle (alpha-SM) actin as a marker for myofib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Experiments investigating the effects of α-SMA expression on fibroblast migration have produced conflicting results. Lung fibroblasts expressing large amounts of α-SMA exhibited increased migratory activity towards fibronectin [53]. However, other studies demonstrated that fibroblast strains with increased α-SMA expression had reduced migratory capacity and that α-SMA knockdown increased cell motility [54].…”
Section: Discussionmentioning
confidence: 99%
“…Experiments investigating the effects of α-SMA expression on fibroblast migration have produced conflicting results. Lung fibroblasts expressing large amounts of α-SMA exhibited increased migratory activity towards fibronectin [53]. However, other studies demonstrated that fibroblast strains with increased α-SMA expression had reduced migratory capacity and that α-SMA knockdown increased cell motility [54].…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblasts from human ACL that migrated into collagen-glycosaminoglycan matrix express α-SM actin [15]. also, fibroblasts that migrated across Boyden chambers were more likely to express α-SM actin than nonmigrated cells [16]. Furthermore, downregulation of α-SM actin by steroid was associated with inhibition of tendon cell migration [17].…”
Section: Introductionmentioning
confidence: 95%
“…The decrease in vimentin expression might therefore explain the decrease in migration capacity found in PC3‐educated MSCs. αSMA expression in fibroblasts has also been shown to correlate with increased migration and so the decrease in αSMA expression found in PC3‐educated MSCs may also be causative in their decreased migration capacity . Both αSMA and vimentin are structural proteins and vimentin is a mesenchymal cell marker .…”
Section: Discussionmentioning
confidence: 99%